(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Environmentrefers to the sum total of condition and influence that affects the life anddevelopment of organism. The qualitative development and quantitative progressof mankind depends on the quality of environment. Therefore, there are no twoviews about the fact that, it is the primary responsibility of man not only topreserve the environment but also to improve it qualitatively.